Approach to Dehydration in Children - Sert, Sadiye (Current Approaches in Emergency Medicine, 2023)
Dehydration due to gastroenteritis in children is a common condition. Paediatricians can assess the extent of dehydration through a history and physical examination. The severity of electrolyte imbalances and dehydration may be assessed using the results of laboratory tests conducted on a sample of severe cases. The first choice should be oral rehydration solution when a child can be fed orally and has just mild dehydration. Severe dehydration in infants can be deadly or very morbid. In order to restore the whole fluid deficit in severe situations, it should be treated straight soon via parenteral route. Dehydration in children has a good prognosis when properly treated.